Structural differences between human proteins and aero- and microbial allergens define allergenicity. - Helton da Costa Santiago; Sasisekhar Bennuru; José M C Ribeiro; Thomas B Nutman (PLoS ONE, 2012)
The current paradigm suggests that structural homology of allergenic proteins to microbial (particularly helminths) or human proteins underlie their allergenic nature. To examine systematically the structural relationships among allergens and proteins of pathogens (helminths, protozoans, fungi and bacteria) as they relate to allergenicity, we compared the amino acid sequence of 499 molecularly-defined allergens with the predicted proteomes of fifteen known pathogens, including Th2 inducing helminths and Th1-inducing protozoans, and humans using a variety of bioinformatic tools. Allergenicity was assessed based on IgE prevalences using publicly accessible databases and the literature. We found multiple homologues of common allergens among proteins of helminths, protozoans, fungi and humans, but not of bacteria. In contrast, 187 allergens showed no homology with any of the microbial genera studied. Interestingly, allergens without homologues or those with limited levels of sequence conservation were the most allergenic displaying high IgE prevalences in the allergic population. There was an inverse relationship between allergenicity and amino acid conservation levels with either parasite, including helminth, or human proteins. Our results suggest that allergenicity may be associated with the relative "uniqueness" of an antigen, i.e. immunogenicity, while similarity would lead to immunological tolerance.